2018
DOI: 10.3390/ijerph15112545
|View full text |Cite
|
Sign up to set email alerts
|

Health-Related Lifestyle Behavior and Religiosity among First-Generation Immigrants of Polish Origin in Germany

Abstract: Background: Health-related lifestyle behaviors such as smoking, alcohol consumption, physical inactivity and obesity are major cardiovascular risk factors. Previous studies have mostly demonstrated a favorable association between religiosity and these cardiovascular risk factors; however, no studies have investigated this relationship in Polish immigrants. The aim of this cross-sectional study was to examine the association between health-related lifestyle behaviors and religiosity in Polish immigrants in Germ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 46 publications
0
16
0
4
Order By: Relevance
“…Prayers allowed the refugees to find comfort, guidance, and purpose in their difficult life situations and found that prayer could help them reduce the stress they experienced. Belonging to a religious community also provided further social support [33].…”
Section: Coping Strategiesmentioning
confidence: 99%
“…Prayers allowed the refugees to find comfort, guidance, and purpose in their difficult life situations and found that prayer could help them reduce the stress they experienced. Belonging to a religious community also provided further social support [33].…”
Section: Coping Strategiesmentioning
confidence: 99%
“…A healthy lifestyle refers to a series of behavioral patterns through which individuals maintain and promote good health based on certain motivations, norms, abilities, and knowledge about what constitutes healthy, stress relieving, or pleasurable behaviors [10]. Lifestyle involves both health risk behaviors, such as smoking, drinking, and sedentariness [11,12] and health-promoting behaviors, such as physical exercise, interpersonal interaction, stress management, and spiritual growth [13]. Research findings have indicated that health is closely related to people’s lifestyles in a wide range of social contexts.…”
Section: Introductionmentioning
confidence: 99%
“…Клиницисты используют эти понятия в своей исследовательской работе и часто находят корреляции внутренней религиозной ориентации с чувством общего благополучия и положительными исходами заболевания [31][32][33][34][35][36][37][38][39][40]. Так, M. McCullough [41] в ходе обзора 80 источников литературы приходит к заключению о значимости религиозности для развития депрессивных симптомов.…”
Section: влияние религии на развитие и проявления депрессивных расстрunclassified